Lithuania : Issues in Municipal Finance - World Bank (Washington, DC, 2013)
Since the establishment of Lithuania's independence, the country achieved substantial progress in transforming its local governments into independent units of Government: structural reforms to prod intergovernmental relations were made in 1994 and 1997, and will continue in 2002. Nevertheless, several issues remain, requiring particular attention from the Government. First, revenue and expenditure assignment between levels of government, and the degree of central regulation over local finance, needs to be reviewed. Local governments face fiscal constraints, for revenues are centrally collected, and distributed at centrally determined rates. And, although local governments have nominal authority over their expenditures, major items (salaries and welfare payments) are subject to Government control, resulting in local governments being faced with running arrears, or borrowing from the Government or private lenders. Although high per capita jurisdictions are required to share revenues with poorer counterparts, it is not clear that distribution mechanisms actually allocate revenues as needed. Upcoming reforms are likely to change this, but a greater change in the revenue distribution criteria, would be by funding delegated functions, but distributing according to sector-specific indicators of need, as well as budgeting financial availability. Second, financing capital investment may be improved by a greater fiscal autonomy to local governments, and mostly, by improving the quality of financial information, with reforms that include the separation of current, and capital accounts, and the adoption of accrual accounting for expenditures.